Pre-Contract Measures to Avoid Potential Disputes in the New Zealand Construction Industry - Silva PM; Domingo N; Ali NANA (UTS ePRESS, 2025)
The New Zealand (NZ) construction industry suffers from negative implications of disputes in construction projects, similar to other countries. Hence, the importance of avoiding disputes has become a vital topic to discuss and research. Avoiding disputes in construction projects has always been challenging, with limited research on this topic. Notably, no studies have explored potential pre-contract measures to prevent disputes in the New Zealand construction industry. To address this research gap, this study was designed, and it is limited only to construction projects in NZ that followed the traditional procurement path. Fourteen professionals in the NZ construction industry with significant experience and knowledge in construction disputes were interviewed, and the gathered data were analyzed qualitatively. A total of 84 pre-contract measures to avoid potential construction-related disputes were identified under five themes (themes of causes of disputes). The most responsible party/parties and most applicable pre-contract stage/s for each dispute avoidance step are also presented. The clarity of communication, risk management, proper documentation and standardization, review and continuous improvements, and collaboration are the main underlying characteristics of the identified avoidance measures. Among the identified dispute avoidance measures, respondents emphasized clear scope documentation and expectation management meetings as the most significant. The proposed measures could help principals, tenderers, and consultants in New Zealand to minimize potential disputes. Additionally, this study opens avenues for further research into dispute avoidance strategies for other procurement methods (other than the traditional procurement path) and practical approaches to clearly document the construction scope.
Keywords: Construction Disputes; Dispute Avoidance; Pre-Contract Stage; New Zealand Construction